Aging and the cross: Explorations in Deep Incarnation. Issue 4 (10th September 2019) - Simmons, Ernest L.
Abstract: Aging is theologically explored in both creation and the cross through the concept of Deep Incarnation. As a partial extension of Martin Luther's thought, Deep Incarnation affirms God to be intimately involved in the natural processes of all biological creation, including aging, bringing solace, companionship, and hope to the elderly. God conceived as being both in the creation and beyond it (panentheism) allows for divine grace to relate to all creatures from the cellular level on up, including through evolutionary development. Employing the concept of compound theodicy, evolutionary theodicy is also briefly explored.